THE NEGATIVE EFFECTS OF SOCIAL MEDIA USAGE ON BODY IMAGE: A REVIEW STUDY - Velkoska, Cvetanka; Şabani, Yasemin (International Scientific Journal Vision, 2024)
The 21st century is referred to as the "Digital Age." Through the internet, people can quickly access information, keep up with developments worldwide, have fun, and chat with loved ones. The concept of social media, which includes social networks, has become one of the most important parts of the internet today. While the internet provides countless benefits to individuals, it can also bring various harms. One of the primary concerns is body image. The filters provided by social media, flawlesslooking photos, and idealized bodies that are far from reality affect individuals' perceptions of their bodies and create a negative impact. These filters and idealized bodies may lead individuals to struggle with accepting their physical characteristics and attempting to conform to the standards portrayed on social media. The "ideal" body images presented in the media can lead to issues such as disordered eating behavior, body image dissatisfaction, feelings of guilt and shame, unhappiness, anxiety, and depression, especially in women. This study addresses the negative effects of social media networks on body image.